FAKTOR-FAKTOR PENGGUNAAN OUT-OF-POCKET PADA PESERTA BPJS PBI DI KLINIK “ASIH SASAMA” - Azizah Boenjamin; Diah Ayu Puspandari (Journal of Health Service Management, 2022)
Background: The Social Security Administering Body (Badan Penyelenggara Jaminan Sosial, BPJS) established a health system based on Social Health Insurance called the National Health Insurance (Jaminan Kesehatan Nasional, JKN). The current implementation still does not meet one of the Universal Health Coverage (UHC) indicators, namely protection against financial risks due to the high use of Out-of Pocket (OOP). Many JKN participants still choose to seek treatment at the Primary Healthcare (FKTP) they are not registered in, resultingin OOP use.Objective: This study aims to explore the factors that cause the use of OOP in BPJS subsidized scheme participants who seek treatment in Outpatient Primary Clinic "Asih Sasama".Methods: This study uses a qualitative research design by using an analytical method, namely Framework Analysis. This research was conducted at the Outpatient Primary Clinic “Asih Sasama” locatedin Saptosari subdistrict, Gunung Kidul regency, Special Region of Yogyakarta. Researchers selected 15 respondents in this study. The theme of the discussion consists of 3 factors: knowledge, preferences,and roles of health workers.Results: Most of the respondents lack the knowledge and understanding regarding their rights and policies related to participation, especially the right to transfer FKTP. The closer distance from the place of residence, and the faster waiting time are the factors affecting the preferences of respondents to choose treatment using OOP. The role of health workers and village officials is still lacking in providing information to the community.Conclusion: It is necessary to strengthen regulations for implementing the JKN program, especially for PBI participants. There is a need for cooperation between stakeholders to hold outreach activities for the poor. There needs to be a solution to the problem of access in the community.